Utilising a novel surveillance system to investigate species of Forcipomyia (Lasiohelea) (Diptera: Ceratopogonidae) as the suspected vectors of Leishmania macropodum (Kinetoplastida: Trypanosomatidae) in the Darwin region of Australia. (August 2020) - Panahi, Elina; Shivas, Martin; Hall-Mendelin, Sonja; Kurucz, Nina; Rudd, Penny A.; De Araujo, Rachel; Skinner, Eloise B.; Melville, Lorna; Herrero, Lara J.
Abstract: Up until recently, Australia was considered free of Leishmania due to the absence of phlebotomine sandfly species (Diptera: Phlebotominae) known to transmit Leishmania parasites in other parts of the world. The discovery of Leishmania ( Mundinia ) macropodum (Kinetoplastida: Trypanosomatidae) in Northern Australia sparked questions as to the existence of alternative vectors of Leishmania . This has added to the complexity of fully understanding the parasite's interaction with its vector, which is known to be very specific. Previous findings demonstrated L. macropodum infection beyond the blood meal stage in the day-biting midges Forcipomyia ( Lasiohelea ) Kieffer (Diptera: Ceratopogonidae) implicating them in the parasite's life cycle. Currently, there is no conclusive evidence demonstrating this suspected vector to transmit L . macropodum to a naïve host. Therefore, this research aimed to investigate the vector competency of day-biting midge F. ( Lasiohelea ) to transmit L . macropodum utilising a novel technology that preserves nucleic acids. Honey-soaked Flinders Technology Associates (FTA®) filter-paper cards were used to obtain saliva expectorated from biting midges while sugar-feeding. F . ( Lasiohelea ) were aspirated directly off macropods from a known Leishmania -transmission site and were kept in a waxed-paper container holding a honey-coated FTA® card for feeding. Insect identification and Taqman quantitative real-time PCR (qPCR) screening assays revealed L. macropodum DNA in F. ( Lasiohelea ) up to 7 days post field-collection, and in an unidentified biting midge, previously known as F. (Lasiohelea ) sp.1. Moreover, 7/145 (4.83%) of FTA® cards were confirmed positive with L . macropodum DNA after exposure to field-collected F. (Lasiohelea ). Additionally, FTA® cards were found to be a valuable surveillance tool, given the ease of use in the field and laboratory. Overall, our findings support previous reports on L . macropodum transmission by an alternative vector to phlebotomine sandflies. Further studies identifying and isolating infective L. macropodum promastigotes is necessary to resolve questions on the L. macropodum vector. Graphical abstract: The graphical abstract illustrates the life cycle of Leishmania * within a phlebotomine sandfly vector. Infected macrophages containing Leishmania amastigotes are ingested when a sand fly feeds on an infected host (1) . Within the abdominal midgut the amastigotes transform into replicative procyclic promastigotes, which are protected from digestive enzymes by the peritrophic membrane (PM) (2) . The procyclic parasites differentiates into highly motile nectomonads to escape from a broken PM (3). Migrating towards the anterior midgut, nectomonads will attach to the microvilli of the midgut epithelium until reaching the stomodeal valve. To resume parasite replication, the nectomonad promastigotes are transformed into leptomonad promastigotes (4), which can either attach to the cuticle lining of the stomodeal valve as haptomonad promastigotes (5) or differentiate into metacyclic promastigotes (infective form) (5) . The infective Leishmania form will colonise the stomodeal valve and are injected into the host during feeding such as on a blood meal or in this case a honey-coated FTA® card (6) . *Note, the life cycle is described for suprapylarian Leishmania species where development is restricted to the sandfly midgut. Image 1 Highlights: 4.83% of FTA® cards were positive for Leishmania macropodum DNA after exposure to field-collected Forcipomyia ( Lasiohelea ). L. macropodum DNA was detectable on cards after 10 weeks demonstrating their utility in Leishmania surveillance programs. Real-time qPCR confirmed L. macropodum DNA in the previously implicated vector, F. ( Lasiohelea ) sp.1. Our results support previous findings suggesting L. macropodum is transmitted by an alternative vector to the sandfly.